2010
DOI: 10.1016/j.bcp.2009.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and calcium flux as targets of neuroprotection caused by minocycline in cerebellar granule cells

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. A c c e p t e d M a n u s c r i p t 1 2 3 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 56 publications
(73 reference statements)
2
53
1
Order By: Relevance
“…These reports may suggest a general broader effect, especially given the potential antioxidant property of these drugs and, more importantly, the high dosages used by the aforementioned studies. Our results and those recently published by some of us (49) clearly show that at concentrations higher than 10 M, minocycline harbors anti-oxidant properties. Accordingly, it is plausible that some of the effects observed with minocycline or other tetracycline derivatives may be attributed to their anti-oxidant functions.…”
Section: Discussionsupporting
confidence: 88%
“…These reports may suggest a general broader effect, especially given the potential antioxidant property of these drugs and, more importantly, the high dosages used by the aforementioned studies. Our results and those recently published by some of us (49) clearly show that at concentrations higher than 10 M, minocycline harbors anti-oxidant properties. Accordingly, it is plausible that some of the effects observed with minocycline or other tetracycline derivatives may be attributed to their anti-oxidant functions.…”
Section: Discussionsupporting
confidence: 88%
“…It has been shown that VDAC contributes to the processes directly or indirectly by interacting with the involved proteins. On the other hand, VDAC may promote cytoprotection including neuroprotection [77,109]. Thus, VDAC may play a central role in mitochondria dysfunction detected in HD ( Figure 1) and its attenuation and consequently in HD treatment.…”
Section: Potential Role Of Vdac In Hdmentioning
confidence: 99%
“…Therefore, it can be speculated that VDAC may be involved in minocycline transport across the outer membrane as proposed by Cuenca-Lopez et al (2011). Accordingly, it is known that minocycline is able to interact with VDAC (Garcia- Martinez et al 2010). Therefore, it can be also suggested that minocycline interaction with VDAC results in changes of properties of minocycline and/or VDAC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, data shown by Gieseler et al (2009) and Antonenko et al (2010) indicate that minocycline prevents MPP activation because of a direct inhibitory interaction with MPP or due to dissipation of the inner membrane potential by ion channels formed by minocycline in the inner mitochondrial membrane, respectively. Minocycline could also result in MPP modulation by affecting the activity of the voltage-dependent anion-selective channel (VDAC) located in the outer membrane, as well as the mitochondrial respiratory chain at the level of complexes I and IV (Garcia-Martinez et al 2010), adenine nucleotide translocase and mitochondrial ATP synthase (FernandezGomez et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation